Prevalence of sexually transmitted infections among healthy Korean women: Implications of multiplex PCR pathogen detection on antibiotic therapy - Kim, Yoonjung; Kim, Juwon; Lee, Kyung-A (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2014)
In this study, we investigated the prevalence of sexually transmitted infections (STIs) using multiplex real-time PCR assay in healthy Korean women. We also evaluated the risk factors of STIs, and compared the various factors between the STI-positive and the STI-negative groups. A total of 799 endocervical swab samples from healthy Korean women who visited our hospital for general medical check-ups during January 2012 to October 2012 were included. Eight STIs including Human papillomavirus (HPV), Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Mycoplasma genitalium (MG), Mycoplasma hominis (MH), Ureaplasma urealyticum (UU), Ureaplasma parvum (UP), and Trichomonas vaginalis (TV) were detected using Anyplex II STI-7 Detection assay Detection (Seegene, Seoul, Korea) and Hybrid Capture 2 High-Risk HPV DNA test (Digene Corporation, Gaithersburg, MD, USA) according manufacture's protocols. Ninety-seven (12.1%) subjects were positive for HPV. Of 393 (49.2%) subjects were infected with at least one microorganism and a total of 499 STIs were identified. Among the 393 STI-positive subjects, the proportion of single, double and triple infection was 76.3%, 20.4% and 3.3%, respectively. The median age of the STI-positive group (47 years, range 42–52) was younger than the STI-negative group (49 years, range 43–56; P < 0.001). The infection rate of HPV was significantly higher in the STI-positive group (15.8%, 62/393) than the STI-negative group (8.6%, 35/406) (P = 0.002).